The Interdimensional Universe—Part 1: Interdimensionality, the Origin of Unidentified Aerial Phenomena (UAP), and Mechanics of Travel between Planes - Cunningham, Paul (Journal of Scientific Exploration, 2025)
This is the first part of a two-part essay that examines the theoretical and empirical case for the interdimensionality hypothesis—namely, planes of multidimensional reality meet at points in the physical universe through which unidentified aerial phenomena (UAP) travel. Part 1 examines the evidence for the existence of UAP and discusses interdimensionality as both a mathematical/scientific concept and a metaphysical hypothesis. Drawing upon the insights of the philosophical psychology of Jane Roberts, four hypothesized features of interdimensional planes (i.e., non-hierarchical organization, open-ended structure and transactional processes, relative physics, and specialized camouflage pattern) and the presumed mechanics of UAP travel between planes are described. Part 2 examines the physics and metaphysics of interdimensionality and its implications for future space travel and outlines a research protocol for the scientific exploration of likely locations where dimensional planes may make contact with the spacetime structure of our physical universe.